GmTOC1b inhibits nodulation by repressing GmNIN2a and GmENOD40-1 in soybean - Zhang, Yuhang; Cheng, Qun; Liao, Chunmei; Li, Lanxin; Gou, Chuanjie; Chen, Zheng; Wang, Yanan; Liu, Baohui; Kong, Fanjiang; Chen, Liyu (Frontiers in Plant Science, 2022)
Symbiotic nitrogen fixation is an important factor affecting yield and quality of legumes. Nodulation is regulated by a complex network comprising several transcription factors. Here, we functionally characterized the role of a TOC1 family member, GmTOC1b, in soybean (Glycine max) nodulation. RT-qPCR assays showed that GmTOC1b is constitutively expressed in soybean. However, GmTOC1b was also highly expressed in nodules, and GmTOC1 localized to the cell nucleus, based on transient transformation in Nicotiana benthamiana leaves. Homozygous Gmtoc1b mutant plants exhibited increased root hair curling and produced more infection threads, resulting in more nodules and greater nodule fresh weight. By contrast, GmTOC1b overexpression inhibited nodulation. Furthermore, we also showed that GmTOC1b represses the expression of nodulation-related genes including GmNIN2a and GmENOD40-1 by binding to their promoters. We conclude that GmTOC1b functions as a transcriptional repressor to inhibit nodulation by repressing the expression of key nodulation-related genes in soybean.